Pengaruh Kombinasi Pupuk Organik (Sampah Sayuran), Urea dan TSP Terhadap Kelimpahan Zooplankton dalam Media Rawa Gambut - Syafriadiman, Syafriadiman; Hasibuan, Saberina; Pamukas, Niken Ayu (Fakultas Perikanan dan Kelautan Universitas Riau, 2016)
Peat soils have the poor water quality, due to its low pH, wich ranges between 3-5, reddish-brown color of the water and minerals and contains very few ground-state nutrient-poor ponds. Household waste can not be used. This study was conducted in Faculty of Fisheries and marine Sciences University of Riau. The results shows that the grade of NPK was very significant effectively on zooplankton abudnance and the species of zooplankton were found from all the treatments consisted of for classes, namely Protozoa, Rotatoria, Crustacea and Insecta. Types of zooplankton derived from protozoa class consists of 4 types namely Coccomonas sp, Euglena sp, Ochromonas sp and Pleodarina sp, whereas Rotatoria class consists of two types of Brachionus angularia and Keratella cochlearis, types of classes crustacea consists of 3 types namely Cyclops sp, Moina sp, and Daphnia sp. The first population peak abundance in all treatments at 12th day with the total abundance in each treatmen of P0 (1,947 ind/l), P1 to (4,623 ind/l), P2 to (9,490 ind/l), P3 (6,327 ind/l). While the second peaks abundance population in all treatments occurred 26 day total abudance in each treatments is P0 (3,772 ind/l), P1 (6,813 ind/l), P2 (13,505 ind/l), P3 (11,193 ind/l). Based on total abundance of 14 times sampling the highest abudance was acieved by P2 treatment (9,490 ind/l)) the 12th day, whereas the second-highest of total abudance of P2 occurred at 26th day (13,505 ind/l).